2017
DOI: 10.3847/1538-4357/835/2/177
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Magnetars Mimicking 56Ni-Powered Light Curves in Type IC Superluminous Supernovae

Abstract: Many Type Ic superluminous supernovae have light-curve decline rates after their luminosity peak which are close to the nuclear decay rate of 56 Co, consistent with the interpretation that they are powered by 56 Ni and possibly pair-instability supernovae. However, their rise times are typically shorter than those expected from pair-instability supernovae, and Type Ic superluminous supernovae are often suggested to be powered by magnetar spin-down. If magnetar spin-down is actually a major mechanism to power T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…The high fitting quality of the magnetar+ 56 Ni model can be most easily appreciated by comparing the reproduced light curves of SN 2002ap by these two models. The situation of SN 2002ap in the pure-magnetar model is similar to SN 1998bw in this same model, see Figure 8 of Moriya et al (2017). The ejecta masses given by the pure-magnetar model are frequently unreasonable, e.g.…”
Section: Alternative Models?mentioning
confidence: 82%
“…The high fitting quality of the magnetar+ 56 Ni model can be most easily appreciated by comparing the reproduced light curves of SN 2002ap by these two models. The situation of SN 2002ap in the pure-magnetar model is similar to SN 1998bw in this same model, see Figure 8 of Moriya et al (2017). The ejecta masses given by the pure-magnetar model are frequently unreasonable, e.g.…”
Section: Alternative Models?mentioning
confidence: 82%
“…6 shows the magnetar model can mimic the 56 Ni-powered lightcurve very well. As discussed in Moriya et al (2017), they found that most 56 Ni-powered lightcurves can be reproduced by magnetars that require the magnetar spin-down to be by almost pure dipole radiation with the breaking index close to 3.…”
Section: Bolometric Lightcurve and Model Fitsmentioning
confidence: 98%
“…However, the capability of a magnetar to mimic radioactive decay would require a pure dipole radiation and a narrow set of fine-tuned parameters, in particular for the magnetic field and Ni masses (Moriya et al 2017). In Figure 14, we display the space parameter where a magnetar (in the dipole case) can mimic the radioactive 56 Co decay from Moriya et al (2017), and compare it with the results from our magnetar fit on the SLSN light curves. The reference time intervals are derived from the observed times after peak where the SLSN decay follows the radioactive rate (Figure 10) and using the explosion times from the magnetar fits to the data (Figure 21).…”
Section: Magnetar Modelingmentioning
confidence: 99%
“…The late-time decays expected within the magnetar scenario can, under certain circumstances, mimic the radioactive 56 Co decay (e.g., Moriya et al 2017). We further discuss this in Section 5.8.…”
Section: Decay Ratesmentioning
confidence: 99%
See 1 more Smart Citation